Exploring the Criterion Validity of Pragmatic Person-Centered Care/Culture Change Measures. (December 2022) - Kunkel, Miranda C.; Madrigal, Caroline; Moore, Reese; Bowblis, John R.; Straker, Jane; Nelson, Matt; Van Haitsma, Kimberly; Abbott, Katherine M.
Background: Nursing homes (NHs) are required to provide person-centered care, efforts often folded into broader culture change initiatives. Despite the known benefits of culture change, it is difficult to measure. This study aims to assess the criterion validity of the Preferences for Everyday Living Inventory (PELI) Implementation Indicator with other culture change measures. Methods: Using data from Ohio-based NHs ( n = 771), logistic regression techniques demonstrated the relationship between the PELI Implementation Indicator and two validated culture change measures, the Resident Preferences for Care (RPC) and Certified Nursing Assistant (CNA) Empowerment scales. Results: There was a significant relationship between the two scales and complete PELI implementation holding all other variables constant. The RPC and CNA Empowerment scales were significantly associated with complete PELI implementation. Discussion: Findings suggest that the PELI Implementation Indicator can be used as a pragmatic indicator of a community's adoption of person-centered care and culture change.